Antimicrobial edible coatings and films from micro-emulsions and their food applications - Guo, Mingming; Yadav, Madhav P.; Jin, Tony Z. (International journal of food microbiology, 2017)
This study focused on the use of antimicrobial edible coatings and films from micro-emulsions to reduce populations of foodborne pathogens in foods. Corn-Bio-fiber gum (C-BFG) was used as an emulsifier with chitosan. Allyl isothiocyanate (AIT) and lauric arginate ester (LAE) served as antimicrobials. Micro-emulsions were obtained from a solution consisting of 1% chitosan, 0.5% C-BFG, and 1–4% AIT or LAE which was subject to high pressure homogenization (HPH) processing at 138MPa for 3cycles. Coatings and films produced from the micro-emulsions had micro-pores with sizes ranging from 100 to 300nm and micro-channels that hold antimicrobials effectively and facilitate the release of antimicrobials from the center to the surface of the films or coatings, thus enhancing their antimicrobial efficacy. The coatings and films with 1% AIT reduced populations of Listeria innocua by over 5, 2, and 3 log CFU in culture medium (Tryptic soy broth, TSB), ready-to-eat meat, and strawberries, respectively. The coatings and films with 1% LAE reduced populations of Escherichia coli O157:H7 and Salmonella spp. by over 5 and 2 log CFU in TSB and strawberries, respectively. This study provides an innovative approach for the development of effective antimicrobial materials to reduce food borne pathogenic contaminants on ready-to-eat meat, strawberries, or other food. •Antimicrobial edible coatings and films made from micro-emulsions by high pressure homogenization•Micro-pores and micro-channels in coatings and films enhanced antimicrobial efficacy•Coating and film significant reduced foodborne pathogens in deli meat and strawberries